2022
DOI: 10.1155/2022/7506189
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Soil Quality for Different Types of Land Use Based on Minimum Dataset in the Typical Desert Steppe in Ningxia, China

Abstract: When the grassland ecosystem is under investigation, soil quality indexes (SQIs) are constructed to evaluate soil quality substantially, especially in desert grasslands and other ecologically fragile areas. This research used the total dataset (TDS), minimum dataset (MDS), approaches dealing with selecting better indexes, and scoring methods utilizing linear and nonlinear expressions to assess the typical desert grasslands in Yanchi County, Ningxia, China. The utilization of four different lands such as forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
0
5
0
1
Order By: Relevance
“…Overall, vegetation restoration in the Loess Plateau significantly increased SOC ( p < 0.05). Tian et al (2022) showed that vegetation restoration had a significant impact on SOC storage; vegetation restoration directly increased carbon input into soil and thus increased soil carbon storage; further, it could indirectly improve SOC by affecting the physical and chemical properties of the soil. SOC content depends on the carbon input of vegetation litter, root exudates, dead roots, and the carbon output produced by soil respiration (Xu, Liu, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, vegetation restoration in the Loess Plateau significantly increased SOC ( p < 0.05). Tian et al (2022) showed that vegetation restoration had a significant impact on SOC storage; vegetation restoration directly increased carbon input into soil and thus increased soil carbon storage; further, it could indirectly improve SOC by affecting the physical and chemical properties of the soil. SOC content depends on the carbon input of vegetation litter, root exudates, dead roots, and the carbon output produced by soil respiration (Xu, Liu, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the range of 1011.4-2092 m above sea level, the response ratio of SOC increased with increasing altitude. Further, in the range of 0-45 slope, the response ratio of SOC increased with increasing slope.4 | DISCUSSION4.1 | Response of SOC to vegetation restorationOverall, vegetation restoration in the Loess Plateau significantly increased SOC (p < 0.05) Tian et al (2022). showed that vegetation restoration had a significant impact on SOC storage; vegetation restoration directly increased carbon input into soil and thus increased soil carbon storage; further, it could indirectly improve SOC by affecting the physical and chemical properties of the soil.…”
mentioning
confidence: 90%
“…Каталазна активність − доволі стійкий та інформативний показник у діагностиці ґрунтів. Значення активності цього ферменту використовують під час вивчення різних типів ґрунту як для характеристики їх біологічних властивостей, так і оцінювання впливу різних чинників на екологічний стан ґрунтової системи (Ying Tian et al, 2022). Встановлено тісний зв'язок каталазної активності і кислотності ґрунту, виявлено підвищення її активності за зростання енергозапасів ґрунтів, які визначаються вмістом органічної речовини (Дем'янюк, 2017).…”
Section: вступunclassified
“…It is necessary to comprehensively evaluate the physical, chemical, and biological characteristics to increase the accuracy of the evaluation [9]. In recent years, many researchers have conducted extensive research on soil quality evaluation methods [10][11][12]. Model methods, such as vague mathematics and dimensionality reduction, have been introduced into soil quality research at different spatial and temporal scales including ecological restoration areas, artificial forest land, and mixed forest land [13,14].…”
Section: Introductionmentioning
confidence: 99%